Differential plating medium for quantitative detection of histamine-producing bacteria. - Niven, C F (Appl Environ Microbiol, 1981)
A histidine-containing agar medium has been devised for quantitative detection of histamine-producing bacteria that are alleged to be associated with scombroid fish poisoning outbreaks. The responsible bacteria produce a marked pH change in the agar, with attendant color change of pH indicator adjacent to the colonies, thus facilitating their recognition. Proteus morganii and Klebsiella pneumoniae were the two most common histidine-decarboxylating species isolated from scombroid fish and mahi mahi.